2017
DOI: 10.1177/2156587217718750
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Autonomic Function Investigations in Hemophiliacs on Homoeopathy Medications Using Impedance Plethysmography

Abstract: Background.Status of autonomic homoeostasis in hemostasic disturbances due to hemophilia needs to be studied.Objectives.To compare autonomic nervous system markers measured by heart rate variability (HRV) and blood flow variability (BFV) in hemophiliacs and healthy age-matched control population using medical analyzer system.Design.Cross-sectional study.Settings.Motiwala Homoeopathy Medical College, and Hemophilia Clinics, Nashik.Subjects.Eighty subjects.Interventions.Nil.Outcome Measures.Autonomic function ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The study done by Kundu et al [25] about the investigations of the autonomic function in hemophiliacs using Impedance Plethysmography, revealed that higher time domain parameter rMSSD for blood flow variability in hemophiliacs as compared with healthy controls that may be reflecting peripheral vascular compensation for reduced vagal activity in the studied patients.…”
Section: Resultsmentioning
confidence: 88%
“…The study done by Kundu et al [25] about the investigations of the autonomic function in hemophiliacs using Impedance Plethysmography, revealed that higher time domain parameter rMSSD for blood flow variability in hemophiliacs as compared with healthy controls that may be reflecting peripheral vascular compensation for reduced vagal activity in the studied patients.…”
Section: Resultsmentioning
confidence: 88%
“…Homoeopathic medicines have been proved effective in reducing the bleeding episodes in PWH as well as managing the acute bleeding episodes. [15][16][17][18][19][20][21][22][23][24][25] In such scenario the homoeopathic medicines in reduction of cost of care in PWH needs to be evaluated.…”
Section: Introductionmentioning
confidence: 99%